Comparación del índice de higiene oral posterior a la aplicación de la técnica visual de retroalimentación y convencional en niños de 6 a 9 años de un centro educativo público en el distrito de Ate – Vitarte en el año 2013 - Flores Ventocilla, Kathleen Mayte (2014)
Objective: To compare the oral hygiene index after application of visual feedback and conventional technique in children of 6-9 years, a public school district of Ate -Vitarte in 2013. Materials and Methods: A quasi-experimental study design type, for which a total of 59 children were assessed at ages 6 and 9, with 33 women and 26 men was conducted. Participants were divided into two groups: group A was given disclosing tablets plaque for use at home during the evenings for a total of 28 days and group B was the control, which were not provided the disclosing tablets. In the first date, group A and B received plaque disclosing tablets, which were to be used in the first session. Only the A group, with the help of a mirror facial, verified areas in which their brushing was poor. Oral hygiene instruction to all participants of both was performed using media on which it is explained on the tooth brushing technique as Bass, caries and periodontal disease. Index oral hygiene Green and Vermillion was used and recorded in the data collection sheet. Subsequently, preceded to present them a teethbrush and toothpaste, which was used to remove the soft plaque and some participants used hand tools to remove calcified plaque. Oral hygiene index at 7 and 28 days was evaluated. Results: There were no statistically significant differences between the use of visual feedback technique and the conventional technique. Also, no association between age and gender regarding techniques was found. Conclusions: Both techniques decrease the oral hygiene index equally in children aged between 6 and 9 years. Also, no association between age and gender was found.